The Role of the Corporate Penalty System on Environmental Regulation - Rais Torodji (Journal of Human Rights, Culture and Legal System, 2023)
The enforcement of the punishment system against corporations for environmental crimes has been unfair, including eliminating environmental permits and minimizing public participation, blurring strict liability or absolute responsibility, centralized supervision, minimizing administrative sanctions, removing corporate criminal liability, and eliminating the ecological organizational lawsuit scheme. The punishment system for corporations in environmental crimes is unjust because the threat of punishment is not proportional to the impact of the act, blurring the norm of strict liability, reducing corporate criminal liability, and forming Law Number 11 of 2020 concerning Job Creation (Job Creation Law) without following law and regulation principles. Reforming the sentencing system by amending the Job Creation Law can help solve the environmental cluster's punishment and law enforcement issues and strengthen environmental supervision by optimizing PPLH capacity through a merit system, management based on transparent and accountable rules, policies, strategies, and programs, and information on superannuation results can help.